Business forecasting with accompanying Excel-based ForecastX software - Wilson, J. Holton (McGraw-Hill/​Irwin, 2007)
This book provides a great overview of the more commonn Excel-based forecasting methods. Though it is designed as a text book, there is enough detail and enough examples to allow you to self-teach the subject. There are one or two significant typographical errors in the later chapters which can lead to frustration. The included software is excellent but you have to make sure that you have the version that runs on your system. The 5th edition does not work well with Excel 2007 but the just-released 6th edition does. The 6th edition also has a chapter on data mining that is not in older versions.